A Woman's Calling (London : National Association of Local Government Officers)
1937 1937 1930s 13 pages Choice of a Career Under existing conditions in the local government service there are two main avenues open to those who aspire to a nursing career :— (i) Hospital and Institutional Appointments Administrative and Nursing Staffs Almoners Dieticians Sister Tutors Teaching Midwives (ii) Public Health Appointments Clinic Staffs Dental Nurses Health Visitors Masseuses Midwives and Teaching Midwives Pharmacists and Dispensers School Nurses Tuberculosis Visitors The Association desires to see the greatest possible degree of interchangeability between appointments on the preventive (public health) side and the curative (hospital) side, to the advantage of the service and to the staffs concerned. The Start of a Career The establishment in 1919 of the General Nursing Councils gave nursing a definite professional status. These Councils maintain a state register of nurses who have satisfied the examiners after a course of training as a probationer nurse in a general hospital over a period of three or four years. There is a supplementary part of the register for male nurses and other supplementary parts containing the names of those trained in the nursing of (a) children, (b) mental diseases, and (c) infectious diseases. 3 292/54.73/2/1